2004
DOI: 10.1126/science.1100658
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC-Mediated Editing of Viral RNA

Abstract: Retroviral DNA can be subjected to cytosine-to-uracil editing through the action of members of the APOBEC family of cytidine deaminases. Here we demonstrate that APOBEC-mediated cytidine deamination of human immunodeficiency virus (HIV) virion RNA can also occur. We speculate that the natural substrates of the APOBEC enzymes may extend to RNA viruses that do not replicate through DNA intermediates. Thus, cytosine-to-uracil editing may contribute to the sequence diversification of many viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
229
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 235 publications
(238 citation statements)
references
References 8 publications
5
229
2
1
Order By: Relevance
“…[36][37][38][39] Rat APOBEC1 (rA1) was selected, because a recent report has demonstrated that this deaminase restricts HIV propagation and can edit HIV RNA. 16 Southern blot analysis confirmed that A3F suppressed viral DNA levels, albeit to a lesser extent than A3G (Fig. 8).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…[36][37][38][39] Rat APOBEC1 (rA1) was selected, because a recent report has demonstrated that this deaminase restricts HIV propagation and can edit HIV RNA. 16 Southern blot analysis confirmed that A3F suppressed viral DNA levels, albeit to a lesser extent than A3G (Fig. 8).…”
Section: Resultsmentioning
confidence: 65%
“…Cytomegalovirus promoter (CMV)-driven expression vectors coding for human A3G, A3F, and rat A1 have been described elsewhere. 8,15,16 A3G-HA is a CMV-driven expression vector encoding A3G fused with a hemagglutinin fusion epitope tag at its carboxy-terminal end. A3G-HA was constructed via polymerase chain reaction (PCR) amplification of A3G complementary DNA from a hepatocyte complementary DNA library using forward primer 5Ј-TAAGC-GGAATTCATGAAGCCTCACTTCAGAAACACA-GTGG-3Ј and reverse primer 5Ј-TAGAAGCTCGA-GTCAAGCGTAATCTGGAACATCGTATGGATAG TTTTCCTGATTCTGCAG-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…6A and D), suggesting that the observed nucleotide changes were induced by A1. Given that rat A1 is also known to edit retroviral RNA, we looked at cDNA extracted from A1 WT -expressing RSCs at 8 hpi at an MOI of 0.01 for evidence of additional deaminase activities (8). Similar to the DNA sequencing results, G3A and C3T transitions in viral cDNA were observed, with the majority of clones containing 1 mutation, while clones with 2 or 3 mutations were also observed ( Fig.…”
Section: Rat Model For Survival Of Encephalitis With Intracranial Hsvmentioning
confidence: 66%
“…A1 homologues are putative inducers of mutations in retrovirus DNA and also in DNA of A1-expressing bacteria (8,24,29,44,49). Thus, to investigate the mechanism of the A1-dependent inhibition of HSV-1 gene expression, we looked at the potential editing of HSV-1 viral DNA.…”
Section: Rat Model For Survival Of Encephalitis With Intracranial Hsvmentioning
confidence: 99%
“…In contrast, RNAediting mechanism (besides those the snoRNA-based base modifications) in other eukaryotes, prokaryotes, and viruses do not make use of RNA components [210,30]. Models for the evolution of the gRNA-based editing process are discussed in [223], a phylogenetic analysis of U-insertion editing [224] suggests that extensive editing is a primitive genetic phenomenon that has disappeared in more modern organism, see also [376].…”
Section: Other Classes Of Small Ncrnamentioning
confidence: 99%